The Brazilian microbiome : current status and perspectives - Pylro, Victor; Roesch, Luiz (Springer, 2017)
Brazilian Microbiome: Current status and perspectives unite a set of distinguished investigators conducting microbiome research and build a comprehensive reference book with up-to-date information regarding the Brazilian microbiome studies and trends. It covers terrestrial and host associated microbiomes, unveiling biological, biotechnological and technical aspects of research. This book is devoted to students and professionals interested in learning techniques for microbiome surveys, including culture-independent approaches, and to better understand the biology of microorganisms in nature, with emphasis to the Brazilian microbiomes.
Keywords: Microbiology -- Brazil.; Brazil.; elektronické knihy; electronic books